Comparison of patient-specific internal gross tumor volume for radiation treatment of primary esophageal cancer based separately on three-dimensional and four-dimensional computed tomography images. Issue 4 (1st June 2014) - Wang, W.; Li, J.; Zhang, Y.; Li, F.; Xu, M.; Fan, T.; Shao, Q.; Shang, D.
Summary: To compare the target volume, position and matching index of the patient-specific internal gross tumor volume (IGTV ) based on three-dimensional (3D ) and four-dimensional (4D ) computed tomography (CT ) images for primary esophageal cancer. Twenty-nine patients with primary thoracic esophageal cancer underwent 3DCT and 4DCT scans during free breathing. IGTVs were constructed using three approaches: combining the gross target volumes from the 10 respiratory phases of the 4DCT dataset to produce IGTV10 ; IGTV2 was acquired by combining the two extreme phases; and IGTV3D was created from the 3DCT -based gross target volume by enlarging the 95th percentile of motion in each direction measured by the 4DCT . 0.16 cm lateral (LR ), 0.14 cm anteroposterior (AP ) and 0.29 cm superoinferior (SI ) in the upper; 0.18 cm LR, 0.10 cm AP and 0.63 cm SI in the middle; and 0.40 cm LR, 0.58 cm AP and 0.82 cm in the lower thoracic esophagus could account for 95% of respiratory-induced tumor motion. The centroid position shift between IGTV10 and IGTV2 was all below 0.10 cm, and less than 0.20 cm between IGTV10 and IGTV3D . IGTV10 was bigger than IGTV2 ; the mean value of matching index for IGTV2 to IGTV10 was 0.87 ± 0.05, 0.85 ± 0.06 and 0.83 ± 0.05 for upper, middle and distal thoracic esophageal tumors, respectively, and just 0.57 ± 0.11, 0.56 ± 0.13 and 0.40 ± 0.03 between IGTV3D and IGTV10 . 4DCT -based IGTV10 is a reasonable patient-specific IGTV for primary thoracic esophageal cancer, and IGTV2 is considered as an acceptable alternative to IGTV10 . However, it seems unreasonable to use IGTV3D substitute IGTV10 .